2019
DOI: 10.14254/2071-8330.2019/12-3/11
|View full text |Cite
|
Sign up to set email alerts
|

Crude oil prices, macroeconomic indicators and the financial sector in Jordan: Dynamic causes and responses

Abstract: This study contributes to the literature on the relationship between fundamental economic factors and stock price movements. We evaluate the relationship between domestic and international macroeconomic indicators and financial sector index in a frontier market that is Amman Stock Exchange (ASE) in Jordan. We employed the ARDL bound testing approach and the VECM Granger causality test to examine long and short run relationships and the direction of causality among the variables. Monthly time series data from J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
1
9
1
Order By: Relevance
“…Therefore, the results show there was a co-integra-tion relationship (significant at 1%) running from the macroeconomic indicators to the industrial index in Jordan. The results are consistent with findings of Abuoliem et al (2019), who found a co-integration relationship between these macroeconomic indicators and financial index in Jordan.…”
Section: Diagnostic Statisticssupporting
confidence: 92%
See 4 more Smart Citations
“…Therefore, the results show there was a co-integra-tion relationship (significant at 1%) running from the macroeconomic indicators to the industrial index in Jordan. The results are consistent with findings of Abuoliem et al (2019), who found a co-integration relationship between these macroeconomic indicators and financial index in Jordan.…”
Section: Diagnostic Statisticssupporting
confidence: 92%
“…Briefly stated, ADF and P-P tests show that LII was non-stationary at I(0) level but became stationary at first difference I (1). Unvarying description of the other macroeconomic indicators can be found in Abuoliem et al (2019). Put another way, the results in both tests were consistent where some variables were stationary at their level, while others were (also) stationary at their first difference.…”
Section: Unit Root Testmentioning
confidence: 75%
See 3 more Smart Citations